Assessing indoor air quality in New York City nail salons. Issue 5 (4th May 2018) - Pavilonis, Brian; Roelofs, Cora; Blair, Carly
ABSTRACT: Nail salons are an important business and employment sector for recent immigrants offering popular services to a diverse range of customers across the United States. However, due to the nature of nail products and services, salon air can be burdened with a mix of low levels of hazardous airborne contaminants. Surveys of nail technicians have commonly found increased work-related symptoms, such as headaches and respiratory irritation, that are consistent with indoor air quality problems. In an effort to improve indoor air quality in nail salons, the state of New York recently promulgated regulations to require increased outdoor air and "source capture" of contaminants. Existing indoor air quality in New York State salons is unknown. In advance of the full implementation of the rules by 2021, we sought to establish reliable and usable baseline indoor air quality metrics to determine the feasibility and effectiveness of the requirement. In this pilot study, we measured total volatile organic compounds (TVOC) and carbon dioxide (CO2 ) concentrations in 10 nail salons located in New York City to assess temporal and spatial trends. Within salon contaminant variation was generally minimal, indicating a well-mixed room and similar general exposure despite the task being performed. TVOC and CO2 concentrations were strongly positively correlated (ρ = 0.81; p < 0.01) suggesting that CO2 measurements could potentially be used to provide an initial determination of acceptable indoor air quality for the purposes of compliance with the standard. An almost tenfold increase in TVOC concentration was observed when the American National Standards Institute/American Society of Heating, Refrigerating and Air-Conditioning Engineers (ANSI/ASHRAE) target CO2 concentration of 850 ppm was exceeded compared to when this target was met.